The accuracy and precision of plain CT chest for diagnosis of anaemia - Mahnoor Hafeez; Sattar, Amjad; Naz, Nasreen (Journal of the Pakistan Medical Association, 2024)
Objective: To determine the accuracy and precision of anaemia diagnosis with plain computed tomography of chest by keeping complete blood count as the gold standard. Method: The cohort study was conducted from January 1 to December 31, 2020, at Dow University of Health Sciences, Karachi, and comprised patients attending the hospital regardless of gender or age. The subjects underwent complete blood count and high-resolution computed tomography scan of chest with 7-day interval. On the basis of haematology, the subjects were divided into anaemic group A and control group B. Blood attenuation measurements and visual perception of the inter-ventricular septum was done blinded to haemoglobin values. Region of interest attenuation cursor was placed within the right ventricular chamber and left ventricular chamber. Quantitative diagnosis of anaemia on computed tomography was done with Hounsfield unit <35 in a chamber. Qualitative computed tomography diagnosis of anaemia was equivalent to inter-ventricular septum visualisation. Accuracy and precision was calculated. Data was analysed using SPSS 17. Results: Of the 124 subjects, n=62(50%) were males and n=62(50%) were females. The overall mean age was 51.45±17.3 years (range: 8-96 years). On the basis of haematology, n=74(59.6%) subjects were in group A and n=50(40.3%) were in group B. The sensitivity, specificity, positive predictive value, negative predictive value and diagnostic accuracy of chest computed tomography for quantitative diagnosis of anaemia were 48.6%, 76.5%, 76.5%, 50.6% and 60.5% respectively. The corresponding values for qualitative diagnosis of anaemia were 55.4%, 88.0%, 87.2%, 57.1%, and 68.5%. Conclusion: There was a high positive predictive value for quantitative diagnosis of anaemia on chest computed tomography with low diagnostic accuracy and moderate reliability. Key Words: Computed tomography, Plain CT, Haemoglobin, Anaemia.